2016
DOI: 10.17146/jair.2015.11.2.2986
|View full text |Cite
|
Sign up to set email alerts
|

Studi Daerah Imbuh Sistem Air Sungai Bawah Tanah Gunungkidul–Yogyakarta Menggunakan Isotop Stabil δ18O dan δ2H

Abstract: Studi Daerah Imbuh Sistem Air Sungai Bawah Tanah Gunungkidul–Yogyakarta Menggunakan Isotop Stabil δ18O dan δ2H. Penelitian air tanah di daerah Gunungkidul, Yogyakarta telah dilakukan menggunakan isotop stabil δ18O dan δ2H. Secara geologi daerah penelitian berada di daerah karst yang didominasi oleh batu gamping (limestone) berupa batuan karbonat dalam bentuk senyawa CaCO3. Penelitian ini dilakukan dengan menempatkan sebanyak lima alat curah hujan di lima lokasi dengan elevasi yang berbeda-beda. Sejumlah sampel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Iffatul Izza Siftianida determined the source of springs in Cijeruk Subdistrict, Bogor Regency, West Java by determining the catchment area with the stable isotope method 18 O and 2 H. This results indicated that springs in Cijeruk Subdistrict, Bogor Regency, West Java are supplied by both rainwater and ground water [13]. Similar studies investigating the origin of groundwater with stable isotopes were also conducted by Kharisma et al in Umbul Cokro Klaten in 2015 [14], Satrio et al in Gunung Kidul [15], Yogyakarta in 2015, and Rusjan et al in Slovenia in 2019 [16].…”
Section: Introductionmentioning
confidence: 55%
“…Iffatul Izza Siftianida determined the source of springs in Cijeruk Subdistrict, Bogor Regency, West Java by determining the catchment area with the stable isotope method 18 O and 2 H. This results indicated that springs in Cijeruk Subdistrict, Bogor Regency, West Java are supplied by both rainwater and ground water [13]. Similar studies investigating the origin of groundwater with stable isotopes were also conducted by Kharisma et al in Umbul Cokro Klaten in 2015 [14], Satrio et al in Gunung Kidul [15], Yogyakarta in 2015, and Rusjan et al in Slovenia in 2019 [16].…”
Section: Introductionmentioning
confidence: 55%